Disaster Risk Reduction in Muslim Residential Areas Based on Community Participation (The Case of Kayupuring Petungkriyono Pekalongan) - Mohammad Irsyad (Islamic Studies Journal for Social Transformation, 2020)
The purpose of this study is to practice the commands in Islam to participate in disaster management throughappropriate mentoring activities to support community members in the community in terms of disaster riskreduction in Kayupuring Village. This study uses the Participatory Action Research method. The research wasconducted in Kayupuring Village with the research subjects of community members, especially those who aremembers of the Tourism Awareness Group (POKDARWIS) and Karang Taruna who have an interest inrealizing an independent village in facing potential disaster threats and increasing the role of the community inprocessing resources to reduce disaster risk. This research resulted in several activities, including 1) Socializationand Formation of a Disaster Resilient Village Volunteer Team (Destana); 2) Revitalization and Disaster RiskAssessment; 3) Self-Assessment and Creation of Evacuation Paths; and 4) Tree Planting.